2018
DOI: 10.1186/s12891-018-2075-x
|View full text |Cite
|
Sign up to set email alerts
|

An update on the prevalence of low back pain in Africa: a systematic review and meta-analyses

Abstract: BackgroundLow back pain (LBP) remains a common health problem and one of the most prevalent musculoskeletal conditions found among developed and developing nations. The following paper reports on an updated search of the current literature into the prevalence of LBP among African nations and highlights the specific challenges faced in retrieving epidemiological information in Africa.MethodsA comprehensive search of all accessible bibliographic databases was conducted. Population-based studies into the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
134
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 68 publications
(238 reference statements)
7
134
6
1
Order By: Relevance
“…Musculoskeletal disorders are a leading cause of health problems, and also contribute substantially to healthcare costs globally (Murray et al, 2012;White & Harth, 1999). It affects populations from both low-and middle-income, and high-income countries (Hoy et al, 2014;Morris, Daniels, Ganguli, & Louw, 2018;Wáng, Wáng, & Káplár, 2016). The global prevalence of musculoskeletal disorders is estimated between 20 and 33% (WHO, 2019); this is consistent with that of low-and middle-income countries (25%) (Jackson et al, 2016).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Musculoskeletal disorders are a leading cause of health problems, and also contribute substantially to healthcare costs globally (Murray et al, 2012;White & Harth, 1999). It affects populations from both low-and middle-income, and high-income countries (Hoy et al, 2014;Morris, Daniels, Ganguli, & Louw, 2018;Wáng, Wáng, & Káplár, 2016). The global prevalence of musculoskeletal disorders is estimated between 20 and 33% (WHO, 2019); this is consistent with that of low-and middle-income countries (25%) (Jackson et al, 2016).…”
Section: Introductionmentioning
confidence: 85%
“…The point prevalence of LBP in low-and middle-income countries notably from Africa is estimated at 39% (Morris et al, 2018); this is higher than high-income countries such as Sweden (23.3%), Denmark (12.0-13.7%) and Canada (28.7%) (Hoy et al, 2010). The high prevalence of LBP observed in Africa may be attributed to the fact that LBP is considered a much lower priority than other health concerns such as HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…LBP affects anyone, of any gender, race or socioeconomic background [5] and has a substantial impact on the overall and nancial wellbeing of an individual and the society [4,7]. Therefore, it was postulated that the burden of LBP would be greater in lower and middle-income countries like those situated in Africa [7,8]. A recent systematic review and meta-analysis published in 2018 revealed that the lifetime, annual and point prevalence of LBP among African nations, was higher than the global LBP prevalence [9].…”
Section: Introductionmentioning
confidence: 99%